Estrés y su incidencia en las relaciones interpersonales de una adolescente de 22 años - Herrera Macías, Jairi Odalis (2023)
This qualitative and descriptive research aimed to analyze the incidence of stress in interpersonal relationships of a 22-year-old adolescent. The research was carried out through a structured interview and clinical observation using the DASS 21 scale and Cohen's perceived stress scale. The patient presented symptoms characterized by difficulty concentrating, irritability, discouragement, muscle tension, and constant headaches, as well as negative thoughts about her situation. Throughout the different sessions, it was observed that the patient felt more comfortable and relaxed, which suggests that the therapeutic intervention could have a positive effect on her emotional well-being. The results of this research could be relevant to understanding how stress affects people's ability to establish and maintain healthy relationships, which could have implications for the design of psychological interventions to improve the quality of life of people affected by stress.